A Review on Cornelia De Lange Syndrome - Chothave Pradnya; DR.Bhangale Charushila (Asian Journal of Pharmaceutical Research and Development, 2025)
Cornelia de Lange Syndrome (CdLS) is a rare genetic condition that affects multiple body systems. It is marked by distinctive facial features, delayed growth, limb differences, and a wide range of cognitive and behavioral challenges. First identified in 1933 by Dutch pediatrician Cornelia de Lange, the syndrome occurs in roughly 1 in 10,000 to 30,000 live births. The severity of CdLS varies widely, from classic, clearly recognizable cases to milder or atypical forms with subtler features. The disorder is mainly caused by mutations in genes related to the cohesin complex—such as NIPBL, SMC1A, SMC3, RAD21, HDAC8, BRD4, ANKRD11, and MAU2—which disrupt gene regulation, DNA repair, and oxidative stress responses, though basic sister chromatid cohesion is usually intact. Individuals with CdLS may display a combination of facial and limb abnormalities, growth restriction, intellectual disability, behavioral difficulties, and problems involving organs such as the heart, digestive system, kidneys, eyes, and reproductive organs. Mosaicism is relatively common and can influence the severity and variability of symptoms, sometimes making diagnosis more challenging. Genetic testing through targeted gene panels or exome sequencing is key for diagnosis, with careful selection of tissue samples to detect mosaic variants. Prenatal diagnosis is possible in families at risk or when ultrasound findings raise suspicion, but interpretation can be complex. Managing CdLS requires a multidisciplinary approach, including nutritional support, surgical interventions, medications for seizures or behavioral concerns, and ongoing therapies such as physical, occupational, and speech therapy. Despite advances in genomic research, some cases remain unexplained, underscoring the complexity of this condition.